A tax system to support sustainability; is it possible? - Kızılgül, Hazel (My University, 2019)
Despite of its globally recognized importance, as it is accepted more widely, the concept of sustainability has continuously suffered from ambiguity. This paper, first, attempts to dissipate clouds even albeit a bit by discussing the concept of sustainable development definition, literature and global performance on achieving it. The global performance is obviously underwhelming even though the governments continuously try to maximize the social welfare with their functions of resource allocation, income distribution and stabilization by using their relevant instruments. And taxation is one of the most important mean used in this road. It should be noted that it is impossible to speak about a perfect tax system which can be beneficial to all of countries and will conclude with sustainable development. Thus, this paper does not aim to show an ideal system but to highlight the importance of a clearer understanding of sustainability and to discuss whether taxation can be a fellow traveller on the road to achieve it. Linking one contentious concept to another can be seen as a fruitless effort, but by restricting the scope of the terms as it only focuses on the sustainability in terms of economic development and taxation from the perspective of progressive income tax, this paper then attempts to question whether to create a tax system to support sustainable development is possible. A detailed analysis is made with this purpose, in which 136 countries are chosen as a sample. A two sectional study has been made by using indicators and thresholds of Holden, Linneraud and Banister (2014)’s “sustainable development space. First we examine sample countries’ status’ in terms of their sustainable development process. 18 countries are on Dimension 1( ecological footprint) and Dimension 2(human development index). There are no high-income or low-income countries that meet both of the thresholds and only 10 countries meet the relevant thresholds, namely, should have achieved sustainable development; Albenia, Azerbaijan, Cuba, Georgia, Indonesia, Jordan, Moldova, Philippines and Uzbekhistan. Second, we analyze Gini coefficients, taxation systems (progressivity, distribution of taxes and percentage tax revenue of GDP) and sustainability performance of these 10 countries case by case. All of these 10 countries have recently improved their tax systems and thus last years’ tax collection percentages are mostly above the world average for high income countries.

Küresel anlamda önemi haylice kabullenilmiş olsa dahi, sürdürülebilirlik kavramına ilişkin bir anlam kargaşası sorunu bulunmaktadır. Tezimizde öncelikli olarak, sürdürülebilirlik kavram tanımını, literatürü ve bu kavrama ulaşmadaki küresel performansı tartışarak, bir nebze de olsa mevcut anlam kargaşası üzerindeki bulutları dağıtma amacı güdülmüştür. Politika yapıcılar, sosyal refahı, kaynak ayrımı, gelir dağılımı ve istikrar araçları ile sürekli olarak maksimize etmeye çalışıyor olsalar da, bu konudaki küresel performansın iç açıcı olmadığı açıktır. Vergilendirme ise bu konudaki en önemli araçlardan biridir. Belirtilmelidir ki, tüm ülkeler için geçerli olacak ve sürdürülebilir kalkınmaya ile sonuçlanacak kusursuz bir vergi sisteminden bahsetmek mümkün değildir. Dolayısıyla, bu çalışma ideal bir vergi sistemi göstermekten ziyade, sürdürülebilirliğin öneminin altını çizerek, kavramın daha net anlaşılması sağlamayı ve vergilendirmenin sürdürülebilirliğe ulaşma da bir yol arkadaşı olup olmayacağını tartışmayı amaçlar. Bu amaçla 136 ülkeyi örneklem alan detaylı bir analiz yapılmış ve Holden, Linneraud ve Banister’ın (2014) “sürdürebilir kalkınma uzayında” çalıştıkları üç farklı eşiği kullanarak iki bölümlü bir detay analiz yapılmıştır.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Sustainability; Sustainable development; Tax system; Progressive taxation; Income taxation; Sürdürülebilirlik; Sürdürülebilir kalkınma; Gelir vergisi; Vergi sistemi; Artan oranlı vergileme